Elective removal of cervical cerclage and onset of spontaneous labor. Issue 1 (3rd April 2014) - Gomes da Costa, Ana O.F.; Clode, Nuno; Graça, Luís M.
Abstract: Objective: To determine the time interval between elective removal of cervical cerclage and onset of spontaneous labor. Methods: A retrospective cohort study was conducted between January 2005 and December 2012 at a tertiary care hospital in Lisbon, Portugal. All singleton pregnancies with a McDonald or Shirodkar cerclage electively removed at 36–37 weeks were evaluated for the time interval between cerclage removal and spontaneous labor. Delivery within 72 hours after cerclage removal was compared between patients with elective cerclage and those with non‐elective cerclage. In the non‐elective group, a sub‐analysis of the results for ultrasound‐ and physical examination‐indicated cerclage was performed. Results: Thirty‐eight women were included. The time interval between cerclage removal and spontaneous labor did not differ significantly between the elective and the non‐elective group (15.6 ± 7.6 vs 10.9 ± 7.4 days; P = 0.063). A higher incidence of delivery 72 hours after cerclage removal was seen in the non‐elective group but this was not significant ( P = 0.061). There were no differences regarding the time interval from elective removal of cervical cerclage to onset of spontaneous labor between ultrasound‐indicated and physical examination‐indicated cerclage. Conclusion: Regardless of the indication for cervical cerclage, the probability of delivery soon after elective cerclage removal is low.